2019
DOI: 10.1088/1755-1315/260/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bamboo strand length on oriented strand board

Abstract: Utilization of non-wood material containing lignocellulose like bamboo Tali could be used for material in the manufacturing of oriented strand board (OSB). This research aimed to evaluate the effect of strand length on OSB quality made from Bamboo Tali. Strand length that used in this research was 5, 10, 15, 20, and 25 cm. The size of the boards. thickness and density target were 25 x 25 cm2, 1 cm, and 0.7 g.cm−3 respectively. OSB was made in three layers with perpendicular strand direction for every layer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The values of MOR parallel to the surface grain of bamboo-based OSB in this study were higher than those of OSB, as reported in previous studies (Suzuki and Takeda 2000;Sumardi et al 2008;Hidayat et al 2013;Febrianto et al 2015;Sulastiningsih et al 2017;Iswanto et al 2019;Lunguleasa et al 2021;Zhuang et al 2022a). All MOR values of bamboo-based OSB in this study met the JIS A 5908 (2015) requirements for type 24-10 (OSB type) particleboard (24 and 10 MPa).…”
Section: The Morsupporting
confidence: 81%
“…The values of MOR parallel to the surface grain of bamboo-based OSB in this study were higher than those of OSB, as reported in previous studies (Suzuki and Takeda 2000;Sumardi et al 2008;Hidayat et al 2013;Febrianto et al 2015;Sulastiningsih et al 2017;Iswanto et al 2019;Lunguleasa et al 2021;Zhuang et al 2022a). All MOR values of bamboo-based OSB in this study met the JIS A 5908 (2015) requirements for type 24-10 (OSB type) particleboard (24 and 10 MPa).…”
Section: The Morsupporting
confidence: 81%
“…The board density followed the targeted standard of 0.6 g/cm 3 . Iswanto et al (2019) found similar densities for other OSB products, showing board densities between 0.61-0.69 g/cm 3 . Another previous study by Cahyadi et al (2012) showed that the density of laminated zephyr bamboo varied from 0.6-0.7 g/cm 3 .…”
Section: Densitysupporting
confidence: 70%
“…As one of the main parameters for strands geometry, the strand length significantly impacts panel performance. Some researchers (Nishimura et al 2001;Barnes 2001;Chirasatitsin et al 2005;Beck et al 2009;Iswanto et al 2019) studied the influence of the strand length on the properties of OSB panels. These studies indicated that the strand length has a significant impact on the bending properties of OSB panels.…”
Section: Introductionmentioning
confidence: 99%